LEGAL REVIEW OF VICTIMS WHO PARTICIPATED IN HUMAN SMUGGLING CRIMES - rasona sunara akbar (Jurnal Ilmiah Kajian Keimigrasian, 2021)
People smuggling is one of the increasingly transnational organized crime. To eradicate the crime of human smuggling, the international community has established a convention of the United Nations Convention Against Transnational Organized Crime (UNTOC) and Protocol Against the Smuggling of Migrants by Land, Sea, and Air, Supplementing the United Nations Convention Against Transnational Organized Crime. One of the responsibility as a UNTOC participant is to preserve and protect the rights of people who are victims of people smuggling. Whereas in reality there are victims of people smuggling who complicity criminal acts. Victims who complicity can shelter under the UNTOC and its Protocol so that they are free from lawsuits. This thesis is to analyze how the legal review of victims who complicity in the occurrence of people smuggling by looking at the f complicity and relations between the perpetrators and victims.